The Relationship between Integration Dimensions among Second Generation Russians in Estonia - Nimmerfeldt, Gerli; Schulze, Jennie; Taru, Marti (Studies of Transition States and Societies, 2011)
This article examines the relationship between structural, cultural, social and identiﬁ cational integration dimensions among second generation Russians in Estonia on the basis of TIES data. The relationship between structural integration and other dimensions is established through cluster analysis, which involves the analysis of the diﬀ erence between means across clusters. In addition, a bivariate correlation analysis is used to determine the relationship between cultural, social, and identiﬁ cational dimensions. The results raise questions regarding the pertinence of linear assimilation theory in the Estonian case. While the cluster analysis reveals a positive relationship between structural and cultural integration, higher levels of social and identiﬁ cational integration are not correlated with higher levels of structural and cultural integration. Second generation Russians retain a strong ethnic identity and socialise primarily with other Russians. A bivariate correlation analysis reveals that there is a relationship between cultural, social and identity-related dimensions. Feelings of belonging to Estonia and distance from both Russia and Russians in Russia are stronger among those with good Estonian language proﬁ ciency. Respondents with strong Estonian language skills also tend to be more socially integrated and to have more Estonian friends.